Thiamine Deficiency Induced Neurochemical, Neuroanatomical, and Neuropsychological Alterations: A Reappraisal - Raffaele Nardone; Yvonne Höller; Monica Storti; Monica Christova; Frediano Tezzon; Stefan Golaszewski; Eugen Trinka; Francesco Brigo (The Scientific World Journal)
Nutritional deficiency can cause, mainly in chronic alcoholic subjects, the Wernicke encephalopathy and its chronic neurological sequela, the Wernicke-Korsakoff syndrome (WKS). Long-term chronic ethanol abuse results in hippocampal and cortical cell loss. Thiamine deficiency also alters principally hippocampal- and frontal cortical-dependent neurochemistry; moreover in WKS patients, important pathological damage to the diencephalon can occur. In fact, the amnesic syndrome typical for WKS is mainly due to the damage in the diencephalic-hippocampal circuitry, including thalamic nuclei and mammillary bodies. The loss of cholinergic cells in the basal forebrain region results in decreased cholinergic input to the hippocampus and the cortex and reduced choline acetyltransferase and acetylcholinesterase activities and function, as well as in acetylcholine receptor downregulation within these brain regions. In this narrative review, we will focus on the neurochemical, neuroanatomical, and neuropsychological studies shedding light on the effects of thiamine deficiency in experimental models and in humans.